Association of skirt size and postmenopausal breast cancer risk in older women: a cohort study within the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS). Issue 9 (24th September 2014) - Fourkala, Evangelia-Ourania; Burnell, Matthew; Cox, Catherine; Ryan, Andy; Salter, Laura Currin; Gentry-Maharaj, Aleksandra; Parmar, Mahesh; Jacobs, Ian; Menon, Usha
Abstract : Objectives: Several studies suggest that overall and central-obesity are associated with increased breast cancer (BC) risk in postmenopausal-women. However, there are no studies investigating changes of central obesity and BC. We report on the association of BC risk with self-reported skirt size (SS; waist-circumference proxy) changes between 20s and postmenopausal-age. Design: Prospective cohort-study. Setting: UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) involving the nine trial centres in England. Participants: Postmenopausal-women aged >50 with no known history of BC prior to or on the day of completion of the study-entry questionnaire. Interventions: At recruitment and at study entry, women were asked to complete a questionnaire. Women were followed-up via 'flagging' at the NHS Information Centre in England and the Hospital Episode Statistics. Main outcome-measure: Time to initial BC diagnosis. Results: Between 2 January 2005 and 1 July 2010, 92 834 UKCTOCS participants (median age 64.0) completed the study-entry questionnaire. During median follow-up of 3.19 years (25th–75th centile: 2.46–3.78), 1090 women developed BC. Model adjusted analysis for potential confounders showed body mass index (BMI) at recruitment to UKCTOCS (HR for a 5 unit change=1.076, 95% CI 1.012 to 1.136), current SS at study entry (HR=1.051; 95% CI 1.014 to 1.089) and change in SS per 10 years (CSS) (HR=1.330; 95% CI 1.121 to 1.579) were associated with increased BC risk but not SS at 25 (HR=1.006; 95% CI 0.958 to 1.056). CSS was the most predictive singe adiposity measure and further analysis including both CSS and BMI in the model revealed CSS remained significant (HR=1.266; 95% CI 1.041 to 1.538) but not BMI (HR=1.037; 95% CI 0.970 to 1.109). Conclusions: CSS is associated with BC risk independent of BMI. A unit increase in UK SS (eg, 12–14) every 10-years between 25 and postmenopausal-age is associated with postmenopausal BC risk by 33%. Validation of these results could provide women with a simple and easy to understand message. Trial registration number: ISRCTN22488978.